The role of the activator rich-W interboundary layer on liquid phase sintering of W-pre-alloy bronze composites of Fe and Co additions - Kahtan S, Muhammed, Dr. (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/